The Impact of Leadership, Motivation and Work Discipline on Employees’ Performance: The Case Study of Muara Telang District Office Kabupaten Banyuasin - Hendra, Yusril Ihzama; Moelyati, Trisniarty Adjeng; Nurahmi, Maftuhah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study aims to determine (1). The influence of leadership, motivation, and discipline on the performance of village officials in the Muara Telang sub-district, Banyuasin district. (2) The influence of leadership on the performance of village officials in the Muara Telang sub-district, Banyuasin district. (3) The effect of work motivation on the performance of village officials in Muara Telang sub-district, Banyuasin district. (4) The effect of work discipline on the performance of village officials in Muara Telang sub-district, Banyuasin district. This research is a quantitative study of data analysis used in this study using multiple linear regression analysis. The population in this study were all employees in 16 villages in the Muara Telang District, totaling 280 employees. The sample used the simple random sampling technique, which is a random sampling technique for the population. By using the Slovin formula, a sample of 165 employees is obtained. The results reveal that leadership, motivation, and work discipline significantly positively affect the employees' performance of village officials in the Muara Telang sub-district, Banyuasin district.